Chinese Medicines for Preventing and Treating Radiation-Induced Pulmonary Injury: Still a Long Way to Go - Ding, Yan; Liu, Yuechao; Li, Hongliang; Li, Yong; Li, Minglun; Liu, Ming; Wang, Xianhe; Cao, Fengjun; Wang, Xuanbin (Frontiers in Pharmacology, 2019)
Thoracic radiotherapy is a mainstay of the treatment for lung, esophageal, and breast cancers. Radiation-induced pulmonary injury (RIPI) is a common side-effect of thoracic radiotherapy, which may limit the radiotherapy dose and compromise the treatment results. However, the current strategies for RIPI are not satisfactory and may induce other side-effects. Chinese medicines (CMs) have been used for more than a thousand years to treat a wide range of diseases, including lung disorders. In this review, we screened the literature from 2007 to 2017 in different online databases, including China National Knowledge Infrastructure (CNKI), Chongqing VIP, Wanfang and PubMed, summarized the effectiveness of CMs in preventing and treating RIPI, explored the most frequently used drugs, and aimed to provide insights into potential CMs for RIPI. Altogether, CMs attenuated the risk of RIPI with an occurrence rate of 15.9% vs. 38.0% (P＜0.001) compared with the control groups. We also found that CMs (alone and combined with western medical treatment) for treating RIPI exerted a higher efficacy rate than that of the control groups (78.35% vs. 58.19%). In the screened literature, 99 CMs in 48 families were used for the prevention and treatment of RIPI. All top four most frequently used CMs were tonics, including Glycyrrhizae radix et rhizome (with a frequency of 40.0%), Ophiopogonis radix (with a frequency of 40.0%), Astragali radix (with a frequency of 31.11%), and Angelicae sinensis radix (with a frequency of 22.22%). Taken together, CMs might have a potential role in RIPI prevention and treatment. However, further high quality investigations in pharmacological effects and underlying mechanisms, and toxicological aspects are warranted.